Redefining infections with trypanosomatids in Neotropical primates: Case study of the white-footed tamarin (Oedipomidas leucopus) - Juliana Tabares-Medina; Katherinne García-Blandón; Gisela M. García-Montoya; Iván Darío Soto-Calderón (International Journal for Parasitology: Parasites and Wildlife)
Trypanosomes are blood parasites capable of infecting nearly any vertebrate. Many Neotropical primates frequently host trypanosomes and are considered potential reservoirs for Trypanosoma cruzi and other human-pathogenic trypanosomatids. However, diagnostic methods originally developed for detecting these trypanosomatids in humans and domestic species must be validated to reliably diagnose infections in non-human primates. Without such validation, taxonomic biases and incorrect assignments of wildlife reservoirs can occur. The white-footed tamarin (Oedipomidas leucopus), a primate endemic to northwestern Colombia, is classified by the World Health Organization as a reservoir of T. cruzi. However, this classification is based on studies with small sample sizes, ambiguous diagnostic methods, and questionable geographic records. In this study, the 18S ribosomal RNA gene was amplified via PCR and sequenced to estimate trypanosome infection rates and identify species in natural populations of O. leucopus across a wide geographic range, as well as in (ex situ) specimens. This molecular approach was also compared with traditional microscopy diagnosis using blood smears. The molecular diagnosis revealed that over 60% of the tested specimens were infected, whereas traditional microscopy resulted in 58% false negatives compared to the molecular method. A Bayesian phylogeny of the 18S gene identified T. minasense as the sole trypanosomatid species present in O. leucopus, with no detections of T. cruzi or other trypanosomatids of concern to human or domestic animal health. This study highlights the risk of overestimating the presence of human-infecting trypanosomes, such as T. cruzi, in tamarins and other vertebrates, and underscores the importance of validating diagnostic methods to accurately assess the zoonotic potential of wild species. Accurate identification of wildlife reservoirs is essential for understanding parasite life cycles and implementing effective management and conservation strategies for primates and other potential reservoirs.